Professional Judgment in Vocational Education: A Scenario-Based Study of Critical Thinking in Associate-Degree Accounting Trainees - Tunç, Cevdet (European Journal of Social Science Education and Research, 2026)
This study aimed to examine the critical thinking and problem-solving skills of associate-degree accounting students through realistic professional scenarios. The research is based on a qualitative design. The participants were fourteen students enrolled in the second year of the accounting program at a vocational college in Turkey’s Western Black Sea Region. Data were collected through scenario-based interviews consisting of three professional scenarios and probing questions corresponding to the six dimensions of Facione’s taxonomy. Responses were scored by two independent coders using a rating scale; inter-coder reliability was calculated using the Cohen’s Kappa coefficient, and the data were also analyzed using thematic analysis. The findings revealed that nine participants fell into the “deep thinker” profile, while five were classified as “developing thinkers.” The highest average score was observed in the Analysis dimension, while the lowest average was found in the Interpretation dimension. The overall average was found to be 2.45 out of 3. This pattern suggests that students are relatively strong in solving a problem and identifying its causes, but weaker in correctly defining the problem from the outset. The lowest average across the scenarios was observed in the software and document mismatch scenario, which required root cause analysis. The thematic analysis identified five themes: evidence-based reasoning, cumulative risk perception, self-correction with expert support, internal control, and professional responsibility. The results indicate that realistic and field-specific scenarios make associate-degree students’ reasoning skills more apparent than context-free tests.
Keywords: professional skepticism, expert–novice differences, vignette method, higher-order thinking, qualitative case study, Facione taxonomy